IMPACT OF PARTICLE SIZE OF KWATHYADRAVYA (DECOCTION POWDER) IN THE PREPARATION OF PHALTRIKADI KWATH - Baghel, Dileep Singh; Kumar Chaudhary, Anand (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The study was aimed to investigate the effects of particle size, vessel used, and extraction time in the preparation of Phaltrikadi kwath. Methods: The particle size of Kwath dravya (solute) was cut into the size of 0.5 cm, 1 cm, 1.5 cm, 2 cm, and coarse powder (pass 60#). The ratios of solvent (water) were 16 times of solute and boiling was done till 1/4th part of the solvent was remain. The provided extraction time was also varied 5.5 to 6 h at temperature range 23Câ€“90Â°C. Phaltrikadi kwath was prepared as per formula mentioned in Sharngadhar samhitaâ€ Madhyam khand 2/77. Results: Total 15 samples of Phaltrikadi kwath were prepared and analyzed for physicochemical and phytochemical parameters, from obtained value, it was confirmed that extraction procedure with varied particle size significantly affected the yield of active pharmaceutical ingredients in prepared Phaltrikadi kwath. Coarse particle sizes can produce a higher yield. Moreover, a longer extraction time produces a higher yield. Conclusion: Kwath (decoction) prepared by particle size 1.5 cm and 2.0 cm may be more therapeutically effective, as it has total solid content more than 6%, it proves that Yavakutaâ€ phenomena of Ayurvedic classics.